Proteomic and Metabolomic Analyses Provide Insights into the Mechanism on Arginine Metabolism Regulated by tRNA Modification Enzymes GidA and MnmE of Streptococcus suis - Gao, Ting; Yuan, Fangyan; Liu, Zewen; Liu, Wei; Zhou, Danna; Yang, Keli; Guo, Rui; Liang, Wan; Zou, Geng; Zhou, Rui; Tian, Yongxiang (Frontiers in Cellular and Infection Microbiology, 2020)
GidA and MnmE, two important tRNA modification enzymes, are contributed to the addition of the carboxymethylaminomethyl (cmnm) group onto wobble uridine of tRNA. GidA-MnmE modification pathway is evolutionarily conserved among Bacteria and Eukarya, which is crucial in efficient and accurate protein translation. However, its function remains poorly elucidated in zoonotic Streptococcus suis (SS). Here, a gidA and mnmE double knock-out (DKO) strain was constructed to systematically decode regulatory characteristics of GidA-MnmE pathway via proteomic. TMT labelled proteomics analysis identified that many proteins associated with cell divison and growth, fatty acid biosynthesis, virulence, especially arginine deiminase system (ADS) responsible for arginine metabolism were down-regulated in DKO mutant compared with the wild-type (WT) SC19. Accordingly, phenotypic experiments showed that the DKO strain displayed decreased in arginine consumption and ammonia production, deficient growth, and attenuated pathogenicity. Moreover, targeted metabolomic analysis identified that arginine was accumulated in DKO mutant as well. Therefore, these data provide molecular mechanisms for GidA-MnmE modification pathway in regulation of arginine metabolism, cell growth and pathogenicity of SS. Through proteomic and metabolomic analysis, we have identified arginine metabolism that is the links between a framework of protein level and the metabolic level of GidA-MnmE modification pathway perturbation.